2017
DOI: 10.1111/petr.13068
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria in pediatric renal transplant recipients

Abstract: Proteinuria has been shown to be an important and potentially treatable risk factor for graft loss. The aim of this study was to evaluate prevalence, etiology, and outcome of proteinuria during the follow-up of children with renal transplantation. We retrospectively reviewed the files of renal transplanted children between 2006 and 2016 in our center. All patients were interpreted with respect to the demographic data and clinical and laboratory features including information about proteinuria. Chi-square test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Further, when it comes to renal transplantation, the urine has provided valuable information, as it is directly attached to the graft, together with its advantage of being non-invasive and less expensive. Indicating structural damage to the glomerular filtration barrier, to the best of our knowledge, proteinuria is assumed to be a powerful risk factor of progressive renal damage and subsequent renal function abnormality in kidney transplant recipients for years [19,20]. Evidence from a paper published a few decades ago, indicated that albuminuria prognostic strength surpasses that of renal function [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, when it comes to renal transplantation, the urine has provided valuable information, as it is directly attached to the graft, together with its advantage of being non-invasive and less expensive. Indicating structural damage to the glomerular filtration barrier, to the best of our knowledge, proteinuria is assumed to be a powerful risk factor of progressive renal damage and subsequent renal function abnormality in kidney transplant recipients for years [19,20]. Evidence from a paper published a few decades ago, indicated that albuminuria prognostic strength surpasses that of renal function [21].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from a paper published a few decades ago, indicated that albuminuria prognostic strength surpasses that of renal function [21]. However, in regard to determine the immune status in recipients, the validity of proteinuria measurements in the kidney transplant recipients remains less conclusive [19]. Cases of COT in kidney transplantation are not that common, and in a study involving a recent Europe-wide survey of a total of 147 centers, there was a cumulative 0.03% incidence of COT in the cumulative experience of 218,913 kidney transplantations [22].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of proteinuria may have an essential value in evaluating the effectiveness of treatment and disease recurrence or progression 1 . Albuminuria and proteinuria, common in kidney transplant recipients, have been associated with deteriorating kidney functions, increased risk for cardiovascular disease, graft loss, and mortality 2,3 …”
Section: Introductionmentioning
confidence: 99%